(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
Petroleum waste disposal in oil-producing regions creates dangerous geotechnical problems affecting desert ecosystems because soil restoration requires extremely long periods. This research investigates how oil contamination affects the geotechnical properties of soils in the Sharara, Elephant, and NC-186 Mutakhendush oil fields in southern Libya. The study utilized simulated datasets and geotechnical testing to analyze changes in strength, density, permeability, and shear parameters in locations experiencing produced water, drilling wastes, and accidental spills. Results indicate that oil contamination transformed soil properties beyond natural background levels, with sites showing moderate to high degradation. Specifically, Unconfined Compressive Strength (UCS) and cohesion at Sharara showed reductions of 58% and 67%, respectively. The analysis of spatial data reveals that operational activities and waste disposal methods create distinct contamination patterns. The research also explores soil stabilization techniques using AI-based geographical mapping to enhance monitoring and remediation planning. Experimental results demonstrated that a combined approach using microbial degradation and Enzyme-Induced Calcite Precipitation (EICP) with lime achieved the highest recovery rates, restoring up to 70% of UCS. These findings emphasize the urgent need for effective petroleum waste management and advanced stabilization strategies to reduce geotechnical risks and protect infrastructure and desert habitats in southern Libya. Integrating AI-assisted mapping with computational tools provides a robust framework for environmental managers to monitor and control geotechnical instability in remote arid regions.